Overweight Impairs Postural Control of Female Night Workers - Narciso, Fernanda Veruska; Dâmaso, Ana R.; Barela, Jose A. [UNESP]; Carvalho, Adriana N.S.; Ruiz, Francieli; de Queiroz, Sandra Souza; Lemos, Vanessa Silva; de-Andrade, Andre Gustavo P.; Tufik, Sergio; De-Mello, Marco Túlio (Thieme, 2023)
Objectives To verify the relationships between sleep duration (Total Sleep Time - TST) and postural control of female night workers before and after shift. As well as, to verify if there is an influence of the body mass index (BMI) on the postural control of these female workers before and after shift. Methods A total of 14 female night workers (mean age: 35.0 ± 7.7 years) were evaluated. An actigraph was placed on the wrist to evaluate the sleep-wake cycle. The body mass and height were measured, and BMI was calculated. Postural control was evaluated by means of a force platform, with eyes opened and eyes closed before and after the 12-hour workday. Results There was an effect of the BMI on the velocity and the center of pressure path with eyes opened before (t = 2.55, p = 0.02) and after (t = 4.10, p < 0.01) night work. The BMI impaired the velocity and the center of pressure path with eyes closed before (t = 3.05, p = 0.01; t = 3.04, p = 0.01) and after (t = 2.95, p = 0.01; t = 2.94, p = 0.01) night work. Furthermore, high BMI is associated with female workers' postural sway (p < 0.05). Conclusion Therefore, high BMI impairs the postural control of female night workers, indicating postural instability before and after night work.
Keywords: circadian rhythms; postural balance; shift work schedule